DYNAMICS OF CHANGES OF C-REACTIVE PROTEIN IN THE SERUM CONTENT IN PATIENTS WITH PHLEGMONS OF THE JAWS AND FACIAL LOCALIZATION AT DIFFERENT TERMS OF TREATMENT - Lokes, K.P.; Lychman, V.O.; Steblovsky, D.V.; Bondarenko, V.V.; Avetikov, D.S. (World of Medicine and Biology, 2021)
C-reactive protein, a highly conserved pentameric protein from the pentraxine family, is a classic acute phase protein and is not only a marker, but also a pro-inflammatory pathogenic factor in inflammatory reactions. C-reactive protein is part of the innate immune response and can influence the immune response via opsonization of microorganisms as well as via activation of the complement cascade. In poly-traumatized and septic patients, the uncontrolled activation of the complement system can lead to an excessive inflammatory reaction with increasing end-organ damage, including via the activation of the complement factor C5. C-reactive protein was the first identified member of the group of so-called “acute phase proteins”. Virtually all acute phase proteins are normal components of blood plasma that have different physicochemical properties. A characteristic feature that combines these proteins into one group is an increase in their concentration in the blood in response to a number of stimuli (infectious diseases, inflammation, trauma, necrosis, tumor growth), which lead to tissue damage. It is proved that the increase in the level of acute phase protein in the blood is due to increased synthesis by the liver with the development of the so-called systemic inflammatory response syndrome.
Keywords: phlegmone; maxilo-facial location; inflammation; protein; chronotype